Myocarditis in monkeypox-infected patients: a case series. (March 2023) - Dumont, Maëlle; Guilhou, Thomas; Gerin, Magdalena; Frémont-Goudot, Guillemette; Nivose, Pierre-Louis; Koubbi, Arnaud; Joly, Véronique; Bouadma, Lila; Yazdanpanah, Yazdan; André, Marie-Hélène; de La Porte des Vaux, Clémentine
Abstract: Objectives: Monkeypox, a zoonotic orthopoxvirus, has spread to many countries in recent months, involving mostly men who have sex with men with multiple partners. Clinical presentation includes skin lesions, systemic signs, and less frequent skin superinfections or anorectal and ophthalmic involvements. We aim to detail cases of myocarditis attributable to monkeypox, an entity that has been poorly described . Methods: This is a descriptive case series reporting three cases of myocarditis that occurred in patients infected with monkeypox in France in 2022. Results: Patients were adult men with no medical history who had skin lesions with positive polymerase chain reaction for monkeypox virus. A few days after the onset of cutaneous signs, patients developed acute chest pain, elevated cardiac markers, and biological inflammatory syndrome compatible with myocarditis. Two patients presented electrocardiogram abnormalities and decreased ejection fraction associated with kinetic disturbances on transthoracic electrocardiography. The last patient had normal transthoracic electrocardiography and normal electrocardiogram, but cardiac magnetic resonance imaging showed segmental inferolateral acute myocarditis. Patients were hospitalized and received cardioprotective treatment. One received antiviral treatment with tecovirimat. Symptoms and laboratory abnormalities rapidly resolved in all patients. Discussion: These cases suggest an association between monkeypox infections and cardiac inflammatory complications. The development of chest pain in an infected patient should not be underestimated and should lead to prompt investigations for myocarditis. Monkeypox infection should also be included in the differential diagnosis of myocarditis, particularly in at-risk patients such as men who have sex with men with multiple partners in whom complete examination for skin or mucosal lesions should thus be performed.